THE ROLE OF PERSONALITY TRAITS OF STARTUP EMPLOYEES IN INFLUENCING PERSON-ENVIRONMENT FIT AND ITS IMPLICATIONS FOR WORK ENGAGEMENT: ORGANIZATIONAL PRODUCTIVITY INSIGHTS - Herman Cahyadi; Haris Maupa; Sarwo Edy Handoyo (Graduate Program of Universitas Tarumanagara, 2024)
Startup companies are consistently required to innovate their business models creatively in order to achieve a disruptive business model. The high level of creativity sets the startup position apart significantly from traditional ventures. Effective human resource management strategies are a fundamental element necessary for the growth of a startup. Startup companies often encounter challenges related to the demands for creativity in their work, resulting in a work engagement that presents a significant challenge for their employees. In practice, the need for creativity in the workplace often leads to a work engagement filled with challenges for its employees. This is closely associated with the appropriate personality traits of employees in the work environment, ensuring that the existing employees have a person-environment fit. This research aims to investigate the influence of personality traits of startup employees on person-environment fit, and its implications for work engagement. This research involved 341 respondents who are startup company Gojek Indonesia employees. The sampling method was conducted using simple random sampling. The confirmatory testing of this study was performed using SEM-PLS (structural equation modeling-partial least square). The analysis results indicate that the personality of startup employees, measured by self-admiration, extraversion, agreeableness, conscientiousness, neuroticism, openness to experience, digital intelligence quotient, optimism, ambiguity tolerance, and flexibility, plays a significant role in influencing person-environment fit and significantly impacts changes in work engagement at Gojek. The suggested managerial implication is the selection of employees with appropriate personality traits, which will create a person-environment fit and consequently lead to high work engagement. This will enhance the opportunities for startups to increase their productivity, particularly in terms of creating creative and innovative products, thereby fostering disruption in the company's business environment.